2019
DOI: 10.1101/652040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitigating biomass composition uncertainties in flux balance analysis using ensemble representations

Abstract: 29The biomass equation is a critical component in genome-scale metabolic models (GEMs): It is 30 one of most widely used objective functions within constraint-based flux analysis formulation, 31 describing cellular driving force under the growth condition. The equation accounts for the 32 quantities of all known biomass precursors that are required for cell growth. Most often than 33 not, published GEMs have adopted relevant information from other species to derive the 34 biomass equation when any of the ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 86 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…Another promising application of our approach is evaluating draft models during the metabolic network reconstruction process. In particular, in building new draft stoichiometric models, the producibility metric, which displays nuanced variability across taxa, could be used as an initial estimate of the biomass composition, to be compared to the reference biomass compositions currently used in most reconstructions (Lakshmanan et al, 2019). More generally, our approach fits into an emerging class of metabolic reconstruction and analysis methods that address uncertainty by statistically sampling ensembles (of environments, as done here; fluxes, as studied extensively [Schellenberger and Palsson, 2009]; or network reconstructions, as recently implemented [Biggs and Papin, 2017; Machado et al, 2018]).…”
Section: Discussionmentioning
confidence: 99%
“…Another promising application of our approach is evaluating draft models during the metabolic network reconstruction process. In particular, in building new draft stoichiometric models, the producibility metric, which displays nuanced variability across taxa, could be used as an initial estimate of the biomass composition, to be compared to the reference biomass compositions currently used in most reconstructions (Lakshmanan et al, 2019). More generally, our approach fits into an emerging class of metabolic reconstruction and analysis methods that address uncertainty by statistically sampling ensembles (of environments, as done here; fluxes, as studied extensively [Schellenberger and Palsson, 2009]; or network reconstructions, as recently implemented [Biggs and Papin, 2017; Machado et al, 2018]).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, when calculating the flux distribution across conditions, biomass was chosen as the primary objective, whereas the secondary objective was set to ATP maintenance, photosystem I, or photosystem II, to reflect the main cellular goals of cyanobacteria. Biomass was chosen as a primary objective to represent the maximization of growth rate and cellular yields ( Feist and Palsson, 2010 ; Yuan et al., 2016 ; Lakshmanan et al., 2019 ), which is a critical consideration for the production of biofuels by cyanobacteria as this informs the substrate uptake rates and maintenance requirements that indicate fundamental cellular growth requirements. The chosen secondary objectives are key pathways involved in energy metabolism during photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…To identify optimal solutions, FBA requires a biologically relevant objective function which represents the metabolic goal of the organism [38], such as maximizing cell growth rate and minimizing total flux. Although biomass production which describes the growth requirements of a cell is widely used in the flux balance analysis [39], several previous studies have demonstrated that flux distributions and predicted cell growth are sensitive to the changes in biomass composition [40,41]. It indicated that accurate representation of biomass is another key to improve the predictive capability of flux balance analysis.…”
Section: Discussionmentioning
confidence: 99%